Legal Transplantation and Funding for Public Electric Vehicle Charging Stations in Achieving Zero Emissions - Muhammad Raihan Yulistio; Satino, Satino (Journal of Law, Politic and Humanities, 2024)
In order to support the use of electric vehicles as a step towards reducing greenhouse gas emissions, adequate and accessible Public Electric Vehicle Charging Stations (Stasiun Pengisian Kendaraan Listrik Umum/SPKLU in Bahasa Indonesia) are required. However, the public still faces difficulties in finding SPKLU. This is due to the absence of specific regulations determining the mandatory distance for the construction of SPKLU and the lack of funding for their development. The research method used is normative juridical, through legislative, conceptual, and comparative approaches. The study utilized secondary data with primary and secondary legal materials. The authors found that the Ministry of Energy and Mineral Resources Regulation No. 1 of 2023 on the Provision of Electric Vehicle Charging Infrastructure does not specifically regulate the distance for SPKLU establishment, necessitating legal transplantation from European Union regulations. Furthermore, the issue of insufficient funding can be addressed through a green bond issuance scheme involving a consortium of State-Owned Enterprises and Private Enterprises.